Elaboration of the Competence Profile of the Residential Child/Youth Care Worker (Global Journal of Human-Social Science, 2014)
This paper describes the steps used to develop a professional competence profile which allows a residential child/youth care worker to perform his or her tasks in an efficient, effective and confident way. Among the strategic and specific competencies, 11 were selected which explain a high percentage of performance (empathy, planning, resistance to stress, responsibility, problem solving, flexibility, collaboration, teamwork, commitment, expertise and communication skills). Once the list of competencies has been established, the behaviors that reflect them are determined and a questionnaire to evaluate the candidates for the position is elaborated.
Keywords: competencies; work behaviours; professional profile; child care worker; youth care worker